De-prosecution and death: a synthetic control analysis of the impact of de-prosecution on homicides - Hogan, Thomas P. (Criminology & public policy, 2022)
Research Summary De-prosecution is a policy not to prosecute certain criminal offenses, regardless of whether the crimes were committed. The research question here is whether the application of a de-prosecution policy has an effect on the number of homicides for large cities in the United States. Philadelphia presents a natural experiment to examine this question. During 2010-2014, the Philadelphia District Attorney's Office maintained a consistent and robust number of prosecutions and sentencings. During 2015-2019, the office engaged in a systematic policy of de-prosecution for both felony and misdemeanor cases. The city recorded the fewest number of criminal prosecutions in modern history, with a 70% reduction in the number of criminal sentencings. Philadelphia experienced a concurrent and historically large increase in homicides. This article employs a difference-in-differences analysis using a synthetic control method to estimate the effects of de-prosecution on the number of homicides in Philadelphia. The potential donor pool is composed of the prosecutors’ offices for the 100 largest cities in the United States over a 10-year period, with a quantitative categorization of the prosecutors’ offices used both as a variable and to exclude cities that may have been subject to a similar de-prosecution treatment. The synthetic control model estimates that de-prosecution has been associated with a statistically significant increase of 74.79 homicides per year in Philadelphia during 2015-2019. Policy Implications As various prosecution policies such as de-prosecution are being implemented across the United States, such policies should be tested for downstream results. The broadscale de-prosecution policy of Philadelphia - particularly for firearm and drug trafficking offenses - appears to have a causal association with a large increase in homicides. The public in Philadelphia will have to make a normative choice between a reduction in the number of prosecutions and an increase in homicides. The government of Philadelphia may consider whether significantly decreased prosecutions by the district attorney's office should result in a decrease in the budget for those services. The overall relationship between de-prosecution and homicides should be reviewed by prosecutors across the nation for consideration in exercising their prosecutorial discretion, given unique local considerations in each jurisdiction.